Development of mutation screening for the molecular diagnosis of tuberous scierosis complex - Sasongko, Teguh Haryo (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2010)
Tuberous sclerosis complex (TSC; OMIM#1911 00) is an autosomal dominant disorder caused by mutations in eitherTSC1 (9q34.13) orTSC2 (16p13.3). TSC is characterized by a broad phenotypic spectrum including epilepsy, mental retardation, skin lesions, and tumors in various organs. The broad phenotypic spectrum reflected the development of hamartomas in multiple organs throughout the body and represents difficulties in the diagnosis of the disease. Mutation analysis in TSC patients is useful1) to confirm a clinical diagnosis of TSC, especially in young patients in whom many clinical features have yet to develop, 2) in families with sporadic cases of TSC, mutation analysis may provide reassurance that the rest of the family members do not carry the mutation. We aimed in this study to develop a protocol for a mutation analysis of TSC1 and TSC2 genes and a database of patients with Tuberous Sclerosis Complex. We employed in this study four different molecular techniques that include denaturing high performance liquid chromatography (dHPLC), DNA Sequencing, multiple ligation-dependent probe amplification (MLPA) and PCR Amplicon Sequencing on MiSeq platform. Using dHPLC and DNA Sequencing we identified 7 nucleotide variations in TSC1 (c.965T>C;pM322T, c. 615 T>C;pS205S, c.1335A>G;p445Giu>Giu, c.1334-55C>G, c.1726T>C;p.L576L and c.210+25A>G) and 2 nucleotide variations in TSC2 (c.2580T>C;p.F860F and c.2639+45G>C) of 10 patients, but none are pathogenic. Using MLPA we identified 3 gross deletions in TSC2 (g.del_ex26-ex31 ;c.2970- 3886del917bp;p.S990R-FsX36, g.del_ex32-41;c.3887-5404del1516bp;p.A1295X and g.del_ex1-ex15) in 3 patients, which are clearly pathogenic. Using PCR Amplicon Sequencing on MiSeq platform we identified 1 variation in TSC1 (c.2071C> T;p.R691X) and 3 variations in TSC2 (c.1361+1 G>A, c.4344insC;p.S1448SFsX1523 and c.3754C>A;p.S1252X) from 5 patients, all of which are pathogenic. Our data suggests that MLPA and PCR Amplicon Sequencing may be more superior as compared to dHLPC and DNA Sequencing in detecting mutations in TSC1 and TSC2 genes. Based on this, for the detection of TSC1 and TSC2 mutations among TSC patients we propose to employ MLPA as first-line molecular diagnostic procedure (1 0-12% coverage) followed by PCR Amplicon Sequencing as a second-line procedure (80% coverage)